Isolation of cancer‐associated fibroblasts and its promotion to the progression of intrahepatic cholangiocarcinoma - Meng Sha; Seogsong Jeong; Bi‐jun Qiu; Ying Tong; Lei Xia; Ning Xu; Jian‐jun Zhang; Qiang Xia (Cancer Medicine)
Abstract Intrahepatic cholangiocarcinoma is a highly fatal tumor characterized by an abundant stromal environment. Cancer‐associated fibroblasts play key roles in tumor growth and invasiveness and have been regarded as a potential therapeutic target. This study was designed to isolate human primary cancer‐associated fibroblasts of intrahepatic cholangiocarcinoma to study tumor‐stroma interactions and to analyze the clinical relevance of alpha‐smooth muscle actin ‐positive cancer‐associated fibroblasts in patients with intrahepatic cholangiocarcinoma. The isolated cancer‐associated fibroblasts were positive for alpha‐smooth actin, fibroblast‐specific protein‐1, fibroblast activation protein, and PDGFR‐β. In addition, cancer‐associated fibroblasts were found to increase proliferation, migration, and invasion of cholangiocarcinoma cells in vitro and promote tumor growth of mice in vivo. Moreover, alpha‐smooth muscle actin‐positive expression of cancer‐associated fibroblasts predicted unfavorable prognosis in patients with intrahepatic cholangiocarcinoma and showed correlation with presence of lymph node metastasis. This study may provide a useful tool to investigate further effect of cancer‐associated fibroblasts on the molecular mechanism of cholangiocarcinoma cells as well as contribution of cancer‐associated fibroblasts in lymphangiogenesis and lymph node metastasis.